STRESS URINARY INCONTINENCE - COMPARATIVE STUDY OF SURGICAL TREATMENT TECHNIQUES MARSHALL-MARCHETTI-KRANTZ AND SUSPENSION ENDOSCOPIC BLADDER NECK - Rodríguez Palma, Paulo (2015)
The authors compare the results of the surgical treatment of stress urinary incontinence (SUI) by the Marshall-Marchetti-Krant and the endoscopic suspension of the bladder neck. In Group I, 30 patients with SUI were operated on by the Marshall-Marchetti-Krantz procedure with a 84% success rate. In Group II, 20 patients with SUI were operated on by the endoscopic suspension of the bladder neck (Stamey procedure) with 95% of cure. The result suggested that the endoscopic suspension of the bladder neck is superior to the Marshall-Marchetti-Krantz procedure in the surgical treatment of stress urinary incontinence.